Survey: Public trust and policy - Positive Energy; Nanos Research (Université d'Ottawa | University of Ottawa, 2018)
Since 2015, Nanos Research has conducted national public opinion surveys in partnership with Positive Energy. This (telephone and online) survey gauged the interest, beliefs and attitudes of 1000 Canadians on current energy policy issues; performance of Canada on developing and implementing energy policies, including the development of oil and gas, relations with Indigenous Peoples, climate change and the transportation of fuels across provinces. This survey also includes views on the building of partnerships to develop energy jointly with Indigenous communities.
Keywords: Climate Change; Indigenous peoples; Energy Policy; Oil and Gas; Renewables; Canada; Public Opinion; Surveys